IMPLEMENTASI PENDIDIKAN KARAKTER ANAK USIA DINI MELALUI PEMBELAJARAN AL-QUR’AN DI SD IT KARAKTER ANAK SHALEH KOTA PADANG - Muaddyl Akhyar; Iswantir M; Ramadhoni Aulia Gusli (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
One of the advantages of technological progress is that it facilitates the rapid dissemination of new information. The availability of detrimental information has a negative impact on children's growth and development. Many videos depict violent and immoral acts, as well as teenagers' social interactions that are contrary to the values of Indonesian society and its culture. The focus of the research is how to incorporate the study of the Koran into the character education program at SD IT Character for Children of Saleh, Padang City. The implementation of character education at SD IT Shaleh Children's Character in Padang City is described using a qualitative research approach. Location in Padang City, West Sumatra, with a sample size of 47 students at the Shaleh Children's Character IT Elementary School. Data collection was carried out through careful observation, in-depth interviews and thorough documentation. Activities at SD IT which aim to instill the values of the Koran in children include teaching the ethics of reading prayers and letters, encouraging five daily prayers, and modeling the life of Muhammad sallallaahu 'alaihi wasallam on how to do it. they must behave well, and reward good behavior and punish bad. Targhib and tarhib methods as well as dialogue and stories are used in forming Al-Qur'an characters for early childhood at SD IT.